Analysis of a multisection and phase-shift-controlled DFB wavelength-tunable optical filter - Low, Andy L. Y.; Ghafouri-Shiraz, H.; Chuah, H. T. (John Wiley & Sons, Ltd., 2000)
We have proposed a new multisection and phase-shift-controlled distributed-feedback wavelength-tunable optical filter structure. The analysis, which is based on the transfer matrix method, reveals that this filter can achieve a tuning range of 32 and 42 Angstrom for grating coupling coefficients of 6 and 10 mm(-1), respectively with an almost constant peak transmissivity (gain) of more than 30 dB. The side-mode suppression ratio (SMSR) ranges from 12 to 30.21 dB. (C) 2000 John Wiley & Sons, Inc.